Peter L. Berger and Thomas Luckmann's social construction of the institutionalization of tolerance values in the Nyadran Perdamaian tradition - Pramono, Muhamad Sidik; Tampake, Tony; Lattu, Izak Y.M; Molewe, Adlan Christember (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2024)
This study aims to examine the social construction process as an effort to internalize the value of tolerance in Nyadran through the addition of the word Perdamaian which is then often referred to as Nyadran Perdamaian. This research is a qualitative study using a case study approach in Krecek Hamlet and Glethuk Hamlet. Research data were obtained through the process of in-depth interviews and literature studies. This research results in an understanding that the social construction of Nyadran Perdamaian gives rise to the internalization of the value of tolerance. The value of tolerance in Nyadran Perdamaian is lived through the creation of social reality with the dialectical triad process of Peter L. Berger and Thomas Luckmann. The appreciation of the value of tolerance by the people of Krecek and Gletuk Hamlets is also pursued through the institutionalization of tradition by changing the name to Nyadran Perdamaian. From the findings of this study, it can be understood that good values in tradition can be maximized through the creation of social reality by individuals or humans. The creation of social reality in Nyadran Perdamaian can also be a prototype for other regions to live the noble values in the tradition. This research also contributes to enriching the study of social construction and provides an understanding that values in tradition can be constructed by individuals so that they can be internalized optimally.